THE MODIFIED METHOD OF RETROSTERNAL TUNNEL FORMATION IN CASE OF ESOPHAGOPLASTY IN CHILDREN - M. G. Chepurnoy; Yu. V. Semernik; A. A. Ayvazyn; Y. V. Khoron’ko; A. N. Kivva; K. A. Novikov (Медицинский вестник Юга России, 2014)
Purpose: to improve retrosternaly conducted artificial esophagus functional properties by manubrium of sternum resection.Materials and methods: a comparative two groups of children examination was performed: first group (53 persons), retrosternal tunnel was made without manubrium of sternum resection and the second group (38 persons) in which manubrium of sternum was resected during retrosternal tunnel formation. The method of resection was described. An X-ray examinations were used to evaluate the function of new-made esophagus.Results: in all patients from the first group a colon diverticula over incisure of sternum were developed, which had clinical and X-ray manifestations, impaired functional properties of artificial esophagus. No such a diverticula revealed in children from the second group.Summary: manubrium of sternum resection in case of retrosternal tunnel formation during esophagoplasty in children excludes the colon compression, colon diverticula formation and improves the food-passing function of new-made esophagus.